Pengembangan E-Pocket Book Berbasis Riset Kesehatan Masyarakat pada Pokok Bahasan Sistem Respirasi - Fany Nurbaithy (Universitas Pendidikan Ganesha, 2024)
Teaching materials are one of the supports in the learning process at school. One of the skills in the 21st century is the use of technology. It is hoped that the development of teaching materials that are integrated with technology, such as e-pocket books, can become an innovative teaching material solution. Apart from that, the delivery of material will also be more useful if it is related to real conditions in everyday life. For example, there are additional results of public health research, especially related to respiratory diseases, in the discussion of the respiratory system material. This research aims to: 1) Analyze the feasibility of an e-pocket book based on public health research on the subject of the respiratory system. 2) Verify the practicality of an e-pocket book based on public health research on the subject of the respiratory system, and 3) Analyze the effectiveness of an e-pocket book based on public health research on the subject of the respiratory system. This research is a type of Research and Development research with the ADDIE (Analysis, design, development, implementation and evaluation) development model. The data collection techniques used were interviews, observation and questionnaires. Based on the research results, it shows that: 1) The feasibility of the e-pocket book was obtained from the development stage with a content validity value of 1 or very feasible, 2) The practicality of the e-pocket book was obtained from the evaluation stage with a CVI (Content Validity Index) value of 0.95 or practical, 3) The effectiveness of the e-pocket book was obtained from the evaluation stage, as many as 97% of students gave very good responses.